2019
DOI: 10.1038/s41467-019-11097-w
|View full text |Cite
|
Sign up to set email alerts
|

Net carbon emissions from African biosphere dominate pan-tropical atmospheric CO2 signal

Abstract: Tropical ecosystems are large carbon stores that are vulnerable to climate change. The sparseness of ground-based measurements has precluded verification of these ecosystems being a net annual source (+ve) or sink (−ve) of atmospheric carbon. We show that two independent satellite data sets of atmospheric carbon dioxide (CO 2 ), interpreted using independent models, are consistent with the land tropics being a net annual carbon emission of and petagrams (PgC) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
122
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(149 citation statements)
references
References 64 publications
25
122
1
1
Order By: Relevance
“…Thus, the forest die-off in California was not attributed to a single extreme dry and warm event in 2015, but rather to a multiyear deep-rooting-zone drought. A similar phenomenon could have occurred over the tropics, where the lack of recovery in the carbon stocks in 2017 could also be explained by cumulative soil moisture depletion, related to low precipitation and enhanced evapotranspiration effects, particularly in the northern regions of tropical Africa (23). These regions also showed precipitation and cumulative soil moisture deficits, as estimated by the cumulative P − ET values ( fig.…”
Section: Discussionsupporting
confidence: 52%
“…Thus, the forest die-off in California was not attributed to a single extreme dry and warm event in 2015, but rather to a multiyear deep-rooting-zone drought. A similar phenomenon could have occurred over the tropics, where the lack of recovery in the carbon stocks in 2017 could also be explained by cumulative soil moisture depletion, related to low precipitation and enhanced evapotranspiration effects, particularly in the northern regions of tropical Africa (23). These regions also showed precipitation and cumulative soil moisture deficits, as estimated by the cumulative P − ET values ( fig.…”
Section: Discussionsupporting
confidence: 52%
“…Compared to peatlands in Equatorial Asia, peat and peat fires in Africa are poorly studied, although recent estimates (Dargie et al 2017;Leifield & Menichetti 2018) indicate that the Congo basin is much richer in peat that presently known (Page et al 2011, FAO/ IIASA/ISRIC/ISSCAS/JRC 2012) and that climate change may induce extensive draught and higher risks of degradation. Palmer et al (2019) reported unexpectedly large net emissions from tropical Africa in recent years especially from western Ethiopia and western tropical Africa, recalling the occurrence there of large soil organic carbon stores and the substantial land use change. Gumbricht et al (2017) recognize that large biases hold in our current understanding of the distribution, area and volumes of tropical peat, and their continental contributions but propose that Southern America could be the region with richest peatlands endowment in the globe.…”
Section: Emissionsmentioning
confidence: 98%
“…Previous studies of atmospheric CH 4 using satellite data tend to be global in scope with a posteriori emission estimates inferred over large continental regions (e.g. Fraser et al, 2013;Pandey et al, 2016;Feng et al, 2017), although some studies use satellite data in regional inversions to infer emissions on smaller regional scales (Turner et al, 2015;Ganesan et al, 2017;Miller et al, 2019). Recent work using GOSAT XCH 4 data has suggested that both atmospheric CH 4 mole fractions and CH 4 emissions from the African continent have increased since 2009 (Maasakkers et al, 2019;Miller et al, 2019).…”
Section: Introductionmentioning
confidence: 99%